Fruit and vegetable intake in the Czech child population - Jakubikova, Marie; Dofkova, Marcela; Ruprich, Jiri (Public health nutrition, 2011)
OBJECTIVE: To describe fruit and vegetable intake of pre-school and school children in the Czech Republic and to provide information about their preferences and dietary habits. DESIGN: Cross-sectional dietary survey conducted by the method of repeated 24 h recall on two non-consecutive days. Usual intakes were calculated for three age categories (4-6, 7-10 and 11-14 years). SETTING: The whole area of the Czech Republic. SUBJECTS: A subgroup of 602 children aged 4-14 years was extracted from the representative sample of respondents participating in a national dietary survey (SISP) realized in the years 2003 and 2004. RESULTS: Estimated average usual intakes of fruit and vegetables were 209 (sd 69) g/d in children aged 4-6 years, 230 (sd 84) g/d in children aged 7-10 years, and 284 (sd 133) g/d and 261 (sd 140) g/d respectively in boys and girls aged 11-14 years. Only 22 % of children had total daily intake of fruit and vegetables of five or more servings on the day of the survey. Fruits were consumed almost two times more often than vegetables in all age groups studied. The majority of fruit consumption comprised apples and bananas, which made up more than 60 % of the whole fruit intake. Fruiting vegetables were the most frequently consumed group of vegetables. CONCLUSIONS: Fruit and vegetable intakes in all age categories were under recommended levels and the diversity of fruit and vegetables consumed by the Czech children was relatively low.
Keywords: fyziologie výživy dětí; školy; sběr dat; preference v jídle; ovoce; Cross-Sectional Studies; Self Report; předškolní dítě; Humans; zelenina; rozhovory jako téma; zpráva o sobě; Czech Republic; Food Preferences; mužské pohlaví; Česká republika; Vegetables; Child, Preschool; Energy Intake; průřezové studie; Diet; Adolescent; Schools; Child Nutritional Physiological Phenomena; Data Collection; ženské pohlaví; lidé; mladiství; Interviews as Topic; dítě; Child; dieta; Fruit; stravovací zvyklosti; Feeding Behavior; Male; energetický příjem; Female